Spread of multidrug-resistant Acinetobacter baumannii and Pseudomonas aeruginosa clones in patients with ventilator-associated pneumonia in an adult intensive care unit at a university hospital - Royer,Sabrina (2015)
Background:In Brazil, ventilator-associated pneumonia (VAP) caused by carbapenem resis- tant Acinetobacter baumanniiand Pseudomonas aeruginosaisolates are associated with signiﬁcant mortality, morbidity and costs. Studies on the clonal relatedness of these isolates could lay the foundation for effective infection prevention and control programs.Objectives: We sought to study the epidemiological and molecular characteristics of A. baumannii vs. P. aeruginosaVAP in an adult intensive care unit (ICU).Methods: It was conducted a cohort study of patients with VAP caused by carbapenem resistant A. baumanniiand P'. aeruginosaduring 14 months in an adult ICU. Genomic studies were used to investigate the clonal relatedness of carbapenem resistant OXA-23-producing A. baumanniiand P. aeruginosaclinical isolates. The risk factors for acquisition of VAP were also evaluated. Clinical isolates were collected for analysis as were samples from the environment and were typed using pulsed ﬁeld gel electrophoresis.Results: Multivariate logistic regression analysis identiﬁed trauma diagnosed at admission and inappropriate antimicrobial therapy as independent variables associated with the development of A. baumanniiVAP and hemodialysis as independent variable associated with P. aeruginosaVAP. All carbapenem resistant clinical and environmental isolates of A. baumanniiwere OXA-23 producers. No MBL-producer P. aeruginosawas detected. Molecular typing revealed a polyclonal pattern; however, clone A (clinical) and H (surface) were the most frequent among isolates of A. baumanniitested, with a greater pattern of resistance than other isolates. In P. aeruginosathe most frequent clone I was multi-sensitive.Conclusion: These ﬁndings suggest the requirement of constant monitoring of these microor- ganisms in order to control the spread of these clones in the hospital environment.